Eye hazard classification according to UN GHS / EU CLP and the severity of eye symptoms caused by accidental exposures to detergents and cleaning products - Scazzola, Roberto; Boeije, Geert; Bøtker Pedersen, Ellen; Brenneman, William; Cagáňová, Blažena; Celentano, Anna; De Coninck, Els; Desel, Herbert; Ebbehøj, Niels; Färber, Elke; Sesana, Fabrizio; Zacharov, Sergej (Regulatory toxicology and pharmacology, 2019)
The use of lower cut-off values/concentration limits for the calculation of mixture classification in UN GHS/EU CLP versus the previous regulatory scheme (EU Dangerous Preparations Directive, DPD), has resulted in an increased number of classifications in the highest eye hazard category. Herein, a semi-quantitative categorisation of severity of eye effects, following accidental human exposures to detergents, was compared to the classification category of the products. Three schemes were evaluated: EU DPD; EU CLP (based on all available data and information, including weight of evidence); and EU CLP (based entirely on the calculation method). As reported by four EU Poison Centres, the vast majority of exposures had caused minor or no symptoms. Classification was a poor predictor of effects in man subjected to accidental exposure. Note however that this is also because effects are not only driven by the intrinsic hazard (as reflected in the classification), but also by the exposure conditions and mitigation (i.e. rinsing). EU CLP classification using all available data and information was more predictive of medically relevant symptoms than the EU CLP calculation method. The latter led to a poorer differentiation between irritating products versus products potentially causing serious eye damage.
Keywords: EU DPD; Poisoning severity score (PSS); detergenty; Irritants; toxikologická centra; Trauma Severity Indices; Detergents and cleaning products; ukazatel závažnosti úrazu; dráždivé látky; Eye hazard classification category; Eye Injuries; Poison Control Centers; Detergents; zvířata; Humans; UN GHS; Accidental eye exposure; EU CLP; poranění oka; lidé; Animals